PELATIHAN DIVERSIFIKASI OLAHAN INOVATIF BERBAHAN TALAS SEBAGAI UPAYA PENINGKATAN NILAI EKONOMI MASYARAKAT - Syamsuri Syamsuri; Pretty Safira; Rizty Wulandari; Fasya Azzahra; Saparina Saparina; Hasria Alang; Abdul Rozi (Universitas Pattimura, 2026)
The residents of Sungai Malaya Village are farmers. One of the agricultural commodities cultivated by the local community is taro. Lack of knowledge and skills causes people to consume taro only as fried or boiled processed products. Therefore, it is necessary to carry out community empowerment activities for farmers, especially women farmers through training in diversified taro processing as an effort to improve skills while increasing the economic value of taro. The purpose of the activity is to increase the economic value of taro through education and practice of innovative diversification of processed tubers and taro flour for women farmers in Sungai Malaya Village. The methods used in this community service are community education and the ABCD (Asset Based Community Development) method, which includes the preparation, implementation and evaluation stages. The ABCD method was chosen because of the assets owned, namely natural resource assets (taro) and human resource sets (the spirit of wanting to change). The results of the service show that the taro processed products taught to partners are taro chips, taro onde-onde, taro sponge cake, and taro brownies. This activity can run smoothly because of the full support of the activity partners. Based on these results, it can be concluded that this activity can increase partners' knowledge and skills regarding innovative diversification of taro tuber processing.